Pelaksanaan Tanggung Jawab DLHK Terhadap Pengelolaan Sampah Berkelanjutan Di TPA Jatiwaringin - Maharani, Rahesha; Ikomatussuniah; Cahyani, Ferina Ardhi (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The increase in waste volume every year in Tangerang Regency has caused the existence of the Jatiwaringin TPA, Tangerang Regency to be increasingly concerning. The Tangerang Regency Government, through the Tangerang Regency DLHK, has the responsibility for waste management as regulated in Article 2 and Article 3 paragraph (1) of Tangerang Regency Regulation Number 1 of 2023 concerning Waste Management. The purpose of this study was to determine the implementation of the Tangerang Regency Government's responsibility in waste management at the Jatiwaringin TPA and the obstacles to the implementation of the Tangerang Regency Government's responsibility in waste management at the Jatiwaringin TPA based on Tangerang Regency Regulation Number 1 of 2023 concerning Waste Management. The theories used are the theory of legal responsibility and the theory of the welfare state. The research method is empirical juridical. The research specifications are descriptive analytical. Data sources are primary data and secondary data. Data collection techniques are by interviews and related documents. Data are obtained and analyzed descriptively with a qualitative approach method. The results of this study are that the Tangerang Regency DLHK has not been optimal in carrying out its responsibility for waste management at the Jatiwaringin TPA using the theory of legal responsibility, namely due to the implementation of roles, including rights and obligations. Although the Tangerang Regency DLHK has attempted the Kurasaki, Kurasakan program and the application of waste management technology to reduce the volume of waste at the Jatiwaringin TPA. However, the use of the open dumping method which is still used at the Jatiwaringin TPA and the minimal provision of waste management facilities and infrastructure as a form of negligence in the role of implementing obligations. The implementation of this responsibility still experiences obstacles, including budget limitations, limited human resources and technology, limited land capacity of the TPA, and lack of public awareness in waste management. These obstacles indicate that the legal responsibility of the Tangerang Regency DLHK in realizing the principles of a welfare state, which should guarantee welfare and social justice for the community, is not yet optimal.